A moderated-mediated model of work alienation and mindfulness at work - Karadas, Georgiana; Hassanie, Souad; Altun, Oezlem; Safaeimanesh, Farzad; Guden, Nafiya (Routledge Journals, Taylor & Francis Ltd, 2025)
This study aims to examine a moderated mediation model of work alienation and mindfulness among employees in line with the conservation of resources theory. Specifically, the impact of emotional intelligence on knowledge hiding mediated by work alienation is assessed. Moreover, the paper assumes that mindfulness moderates the indirect effect of emotional intelligence on knowledge hiding via work alienation. Data were gathered from workers working in five-star hotels in Northern Cyprus and analyzed by AMOS. The findings highlighted the mediating role of work alienation between emotional intelligence and knowledge hiding. Furthermore, the results revealed that mindfulness moderates the indirect impact of emotional intelligence on knowledge hiding via work alienation in the sense that the higher the level of mindfulness is, the stronger the effect of emotional intelligence on reducing work alienation. The paper discusses the implications for theory and practice and provides future research suggestions.
Keywords: Work alienation; knowledge hiding; emotional intelligence; mindfulness